Investigation of a Novel Personal Sampler Material for the Identification of Human Exposure To Semivolatile Organic Compounds - Demirtepe, Hale; Akmermer, Zülfikar; Sofuoğlu, Sait Cemil (My University, 2024)
SVOCs are widespread indoors, where they occur at high levels. Humans spend most of their time indoors and are regularly exposed to these compounds. Various methods exist to assess human exposure to SVOCs. However, a novel personal sampler material, i.e. silicone wristband, has been used for the last decade. Due to its commencing use, the uptake capacity of silicone wristbands for SVOCs still needs to be discovered. This study aims to investigate the SVOC uptake rate and equilibrium partitioning coefficients of silicone wristbands. To achieve this aim, an analysis method for determining SVOCs in silicone wristbands was developed and validated with wristbands worn by academic personnel of IZTECH. The results showed that among polycyclic aromatic hydrocarbons (PAHs) acenaphthylene, among organophosphate esters (OPEs), tris (2-butoxyethyl) phosphate and among phthalate esters, di(2- ethylhexl) phthalate were found as the dominant SVOCs in silicone wristbands. Then, the uptake capacity of silicone wristbands for PAHs was investigated by deploying them in a school environment for 36 days, together with polyurethane foam passive air samplers. The uptake rates varied three orders of magnitude for compounds reaching equilibrium, i.e. acenaphthene, acenaphthylene, fluorene, phenanthrene, and anthracene (0.010 – 25.93 m3/day), while for fluoranthene, chrysene, and pyrene uptake rates were close to each other (0.17 – 0.50 m3/day). Furthermore, silicone wristband-air partitioning coefficients were in the range of 5.93 to 7.43 for acenaphthene, acenaphthylene, fluorene, phenanthrene, and anthracene. Lastly, daily and chronic toxic exposures and lifetime cancer risk for school children were assessed using PUF-PAS concentrations, and no significant risk was identified.

Yarı uçucu organik bileşikler (YUOB) çevrede geniş bir şekilde dağılmış olup, özellikle iç mekanlarda yüksek konsantrasyonlara rastlanmaktadır. İnsanlar zamanlarının çoğunu iç mekanlarda geçirdikleri için bir dizi YUOB'ye maruz kalırlar. İnsan maruziyetini değerlendirmek için çeşitli yöntemler kullanılabilir. Ancak, son on yıldır kullanılan yeni bir kişisel örnekleyici malzeme olan silikon bilekliklerin YUOB 'ler için alım kapasitesi henüz keşfedilmemiştir. Bu çalışmanın amacı, silikon bilekliklerin YUOB alım hızını ve denge dağılım katsayılarını araştırmaktır. Bu amaca ulaşmak için, silikon bilekliklerdeki YUOB'lerin belirlenmesine yönelik bir analiz yöntemi geliştirilmiş ve İYTE akademik personeli tarafından kullanılan bilekliklerle doğrulanmıştır. Sonuçlar, polisiklik aromatik hidrokarbonlar (PAH'lar) arasında asenaftilenin, organofosfat esterler (OPE'ler) arasında tris (2-butoksi etil) fosfatın ve ftalat esterler arasında di(2-etilhekzil) ftalatın silikon bilekliklerde baskın YUOB 'ler olarak bulunduğunu göstermiştir. Daha sonra, PAH'lar için silikon bilekliklerin alım kapasitesi, poliüretan köpük pasif hava örnekleyicileri ile birlikte 36 gün boyunca bir okul ortamında kullanılarak araştırılmıştır. Dengede olan bileşikler için alım hızları üç basamak olarak değişmiştir, yani asenafilen, asenaftilen, florin, fenanten ve antren (0.010 - 25.93 m3/gün), floranten, krisen ve piyren için alım hızları birbirine yakındı (0.17 - 0.50 m3/gün). Ayrıca, silikon bileklik-hava bölünme katsayıları asenafilen, asenaftilen, florin, fenanten ve antren için 5.93 ile 7.43 arasında değişmiştir. Son olarak, okul çocukları için günlük ve kronik toksik maruziyetler ile ömür boyu kanser riski, PUF-PAS konsantrasyonları kullanılarak değerlendirilmiş ve anlamlı bir risk tespit edilmemiştir.
Yarı-uçucu organik bileşiklere maruziyetin belirlenmesinde yeni bir kişisel örnekleyici malzemenin araştırılması
Thesis (Master)--Izmir Institute of Technology, Environmental Engineering, Izmir, 2024
Includes bibliographical references (leaves. 71-88).
Text in English; Abstract: Turkish and English.
Keywords: Volatile organic compounds; Air quality management.